International law archilles: how Asian legitimizes Eurocentric / Siti Nur Amirah Shamsuddin … [et al.] - Shamsuddin, Siti Nur Amirah; Hanapi, Hafizah; Idris, Nurrabiatul Adawiyah; Mohd Naim, Nur'Izzati (Faculty of Law, 2012)
This research focus on the principle of how Asian legitimize Eurocentric in the international law view. As there are questioned and answers that need to be seen on how Asian legitimize the Eurocentric of international law. By having this research done, we can see in a large that Asian has issue in legitimize the Eurocentric of international law in it. It also follows to the Third World countries which within it is Asian. Thus, there is indeed a need to further analyse and examine the Asian participation and approaches in this matters. The issue of how Asian adopt the Eurocentric of international law in it natural law will be further questions and answers. The Third World participation and approaches in Asian countries and international law can be also seen to be discussed in this research. This questions and answers will be look into various ways and views on the international law. However, it must be noted that Asian pays more attention in regards of matter on the human rights of it countries and especially it people. It is submitted that, Asian participation and approaches are based on certain reasons and action in regard of the international law. Therefore, this research can help by analyse and examine how Asian legitimize the Eurocentric.